Parasitic Protozoa found in the skin, gills, and intestines of Patin Catfish (Pangasius hypophthalmus) and Common Carp (Cyprinus carpio) - Veenu Kumar; Arifin Budiman Nugraha; Umi Cahyaningsih; Tara Puri Ducha Rahmani (Journal of Natural Sciences and Mathematics Research, 2021)
The parasitic protozoa found in "Ikan Patin" or a species of Catfish (Pangasius hypophthalmus) and "Ikan Mas" or Common Carp (Cyprinus carpio) are Trichodina sp., Ichthyophthirius sp. and Myxobolus sp. These protozoa have the potential to cause death in fish and economic losses to fish farmers and sellers. This study was conducted to determine the presence of parasitic protozoa on the skin, gills, and intestines of Catfish and Carp. Samples were taken from the Bursa Ikan Hias Laladon or Laladon Ornamental Fish Market in Bogor, Indonesia. Each species was sampled for as many as 30 fish. The skin, gills, and intestines were examined using the native examination method and Lugol staining. Parasitic protozoa were identified based on their morphology, namely size, and shape. The types of parasitic protozoa found on the skin, gills, and intestines of Catfish and goldfish were Trichodina sp., Ichthyophthirius sp., and Myxobolus sp. The parasites were found in skin organs in as many as 29 samples (96.7%) from Catfish and 30 samples (100%) from Carp. The Genera of Ichthyophthirius sp. were found in the gills of 2 samples (6.7%) in Catfish and 1 sample (3.3%) from positive Carp. Myxobolus sp. was found in the intestines of 11 samples (36.7%) from Catfish and two samples (6.7%) from Carp. The species of Trichodina sp. found based on morphology was Trichodina giurusi.©2021 JNSMR UIN Walisongo. All rights reserved.